(طقوس بيليان باسير نوندوي (استكشاف قيم الوسطية الدينية في الحكمة المحلية لمجتمع باسير - Hamsiati Hamsiati; Khaerun Nisa' (Balai Penelitian dan Pengembangan Agama Makassar, 2021)
This research aims to explore the value of religious moderation in the local wisdom of Paser people in Penajam Paser Utara. This research used descriptive qualitative methods with interview techniques, document studies, and field observation. The research conducted in Penajam Subdistrict, Penajam Paser Utara, reveals that one of the local wisdoms of Paser people is oriented towards religious moderation through Belian Nondoi ritual or Belian Paser Nondoi. In practice, the values of religious moderation emerge at the value of cooperation between communities without any difference in the preparation of elian Nondoi rituals, which in the process, the community will gather in Kuta Rekan Tatau to witness that they have the same rights without any difference from each other. All of them will be prayed for their salvation through Soyong which is practiced by Mulung in Belian Nondoi ritual. Belian Nondoi traditional ritual of Paser community can unify the members of different community beliefs, different tribes, languages, and different cultures as well, as a means of unifying the community in Penajam Paser Utara. Thus, the Belian Nondoi ritual needs to be preserved, so that the values of religious moderation contained in it can be maintained and become a tradition in society, especially for the younger generation.